The Influence of Personal Knowledge, Job Procedure and Technology toward Employee Performance at PT Wahana Sun Motor Semarang - Rahmawati, Erlin Fajar; Sulistiyani, Endang -; Inayah, Inayah - (Politeknik Negeri Semarang, 2020)
Employee performance can achieve maximum results if supported by knowledge where the type of knowledge application is personal knowledge, job procedure and technology. This study aims to determine the influence of personal knowledge, job procedure and technology on employee performance at PT Wahana Sun Motor Semarang. This research is quantitative research. The sampling technique used was saturated sampling and the number of samples in the research are 30 respondents. They are employees of PT Wahana Sun Motor Semarang. The data analysis method used was Multiple Linear Regression Analysis. Based on the result of F test, it shows that personal knowledge, job procedure and technology simultaneously had influence on employee performance. The result of the T test shows that personal knowledge and job procedure partially had a significant influence on employee performance, while the technology variable had no significant influence on employee performance. The most dominant variable affecting employee performance is job procedure. Personal knowledge, job procedure and technology contributed to the influence of employee performance by 63.9%, while the remaining 36.1% was influenced by other variables outside of this research model.